2010
DOI: 10.1111/j.1432-2277.2009.00945.x
|View full text |Cite
|
Sign up to set email alerts
|

Should we perform heart retransplantation in early graft failure?

Abstract: Summary Cardiac retransplantation represents the gold standard treatment for a failing cardiac graft but the decision to offer the patient a second chance is often made difficult by both lack of donors and the ethical issues involved. The aim of this study was to evaluate whether retransplantation is a reasonable option in case of early graft failure. Between November 1985 and June 2008, 922 patients underwent cardiac transplantation at our Institution. Of these, 37 patients (4%) underwent cardiac retransplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
(30 reference statements)
1
9
0
1
Order By: Relevance
“…The analysis from our series revealed that retransplantation for graft vascular disease significantly improved 30-day mortality and late survival compared with retransplantation for other conditions. These findings are supported by others, who report similarly good outcomes in patients who had retransplantation for graft vascular disease; 10,11,18,19 however, patients with acute graft rejection or primary graft failure had significantly inferior outcomes. 10,11,18,20 We therefore conclude that allograft failure for acute graft rejection or primary graft failure should be medically managed and the patients possibly excluded from consideration for retransplantation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The analysis from our series revealed that retransplantation for graft vascular disease significantly improved 30-day mortality and late survival compared with retransplantation for other conditions. These findings are supported by others, who report similarly good outcomes in patients who had retransplantation for graft vascular disease; 10,11,18,19 however, patients with acute graft rejection or primary graft failure had significantly inferior outcomes. 10,11,18,20 We therefore conclude that allograft failure for acute graft rejection or primary graft failure should be medically managed and the patients possibly excluded from consideration for retransplantation.…”
Section: Discussionsupporting
confidence: 79%
“…This has also been reported in other studies where shorter intervals between operations significantly increased adverse outcomes. 11,18 Because of this, most authors generally advise against retransplantation less than 1 month after primary transplantation because of clearly inferior outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] This remarkable achievement of modern medicine was made possible with substantial improvements in the field of immunosuppression, infection prophylaxis and surgical techniques. 1,[4][5][6][7][8][9][10][11] Today, heart transplantation is no longer considered an experimental operation, but rather a standard treatment; nevertheless the context has changed substantially in recent years owing to donor shortage.…”
Section: Discussionmentioning
confidence: 99%
“…There have been studied factors related to the receptor (such as age, the reason for the CRT or some comorbidities), technical aspects such as the ischemic time or even the technique used, and characteristics of the donor [5][6][7][8][9][10][11][12][13][14][15], none of them guaranteeing long-term success. The experience gained in each centre, the specific protocol of each group and individual assessment are so far the only variables that appear to influence the outcome in the CRT.…”
Section: Journal Of Clinical and Experimental Research In Cardiologymentioning
confidence: 99%